Optimal reference genes for RT-qPCR normalization in the newborn. (3rd October 2017) - Khanna, P; Johnson, KL; Maron, JL
Abstract: It is difficult to identify reliable reference genes for transcriptomic analyses in biofluids such as saliva. This situation is particularly relevant for the newborn population, where rapid development is associated with dynamic changes in gene expression. Real-time gene expression monitoring holds great promise for elucidating disrupted pathways that result in morbidities unique to this population, such as retinopathy of prematurity, but its impact depends on identifying stable and consistently expressed genes across a wide range of gestational ages. We extracted total RNA from 400 neonatal saliva samples (postconceptional ages: 32 5/7 to 48 2/7 weeks), converted it to cDNA, and pre-amplified and analyzed it by qPCR for three commonly used reference genes, ACTB, GAPDH, and YWHAZ . Relative quantification was determined using the Δ Ct method. Data were analyzed as a whole and also stratified by age and sex. Descriptive statistics and homogeneity of variance were performed to identify optimal reference genes. Data analyzed from all ages and both sexes showed significant expression variation for ACTB, while GAPDH and YWHAZ showed greater stability. Male infants exhibited increased expression variation compared to females for ACTB, but neither GAPDH nor YWHAZ showed significant variance for either sex. We suggest that ACTB is an unreliable reference gene for the newborn population. Males showed significantly more variation in ACTB expression compared to females, which suggests a sex-specific developmental role for this biomarker. By contrast, GAPDH and YWHAZ were less variable and therefore preferable for use in neonates. Our findings may improve the use of reference genes for the RT-qPCR platform in the newborn over a wide range of gestational ages, thereby minimizing the likelihood of erroneous interpretation of gene expression during rapid growth, development, and differentiation.